The idea of a European superstate : public justification and European integration - Morgan, Glyn, 1958- (Princeton University Press, 2005)
Is there a justification for European integration? The Idea of a European Superstate examines this--the most basic--question raised by the European Union. In doing so, Glyn Morgan assesses the arguments put forward by eurosceptics and their critics. In a challenge to both sides of the debate, Morgan argues in support of a European superstate. Unless Europe forms a unitary sovereign state, Europe will remain, so he maintains, weak and dependent for its security on the United States. The Idea of a European Superstate reshapes the debate on European political integration.